Changes in the Runoff of Urumqi Glacier No. 1 Under Climate Change: From Historical Observation to Future Prediction - Jiang, Pei; Wang, Zemin; Yan, Boya; Ai, Songtao; Jin, Shuang (Frontiers in Earth Science, 2022)
This study explores the ice volumes of Urumqi Glacier No.1 from 2013 to 2112 to examine the changes in the runoff of the glacier. Based on the Sixth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC), the changes of the glacier were predicted under the three hypothetical climate scenarios: SSP1-1.9, SSP2-4.5 and SSP5-8.5 scenarios. Results, derived from the Elmer/Ice ice-flow model, showed the increasing runoff till 2040 in the SSP2-4.5 and SSP5-8.5 scenarios, gradually decreasing runoff in the SSP1-1.9 scenario. The glacier areas and ice volumes of two branches will keep declining under all the climate scenarios, including fast reductions until 2080 and slow reductions by the end of the ablation period. Moreover, the east branch (EB) will disappear at the end of the 21st century under the SSP2-4.5 and SSP5-8.5 scenarios. With much mass loss of the EB under all the climate scenarios, the runoff will increase in the early 100-year period and decrease until its being infinitely close to the precipitation, which is similar with that of the west branch (WB). Since 2070, the ice volumes of the WB will contribute more than 50% of the whole glacier volumes under all the climate scenarios. The WB ice volume percentage will reach 100% in 2080 for the disappearance of the EB under the SSP5-8.5 scenario. As the fast retreat of the EB before 2080, the variations of the total runoff will be consistent with that of the EB runoff, and the EB runoff will account for more than 60% of the total runoff before 2070 under all the climate scenarios. Even if, the meltwater of Urumqi Glacier No.1 will be stable from the late 21st century (after 2090), it will decline to approximately 15% of that in 2013. It will greatly influence the runoff of Urumqi River, hence, human life and biodiversity.